2014
DOI: 10.2337/db14-1050
|View full text |Cite
|
Sign up to set email alerts
|

Lowering Body Weight in Obese Mice With Diastolic Heart Failure Improves Cardiac Insulin Sensitivity and Function: Implications for the Obesity Paradox

Abstract: Recent studies suggest improved outcomes and survival in obese heart failure patients (i.e., the obesity paradox), although obesity and heart failure unfavorably alter cardiac function and metabolism. We investigated the effects of weight loss on cardiac function and metabolism in obese heart failure mice. Obesity and heart failure were induced by feeding mice a high-fat (HF) diet (60% kcal from fat) for 4 weeks, following which an abdominal aortic constriction (AAC) was produced. Four weeks post-AAC, mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 73 publications
1
51
0
Order By: Relevance
“…Based on the unaltered expression of SIRT3 but increased expression of GCN5L1, we propose that GCN5L1 may be a key modulator of protein acetylation in the heart during maturation. This notion is supported by our recent studies in which increased GCN5L1 contributes to an increase in acetylation of LCAD in obese mice with heart failure, which, in turn, enhances fatty acid oxidation rates (52). As a proof of the concept, we further demonstrated that the inhibition of GCN5L1 in H9c2 cells via siRNA attenuated the levels of acetylated LCAD and ␤-HAD, as well as total protein acetylation, in parallel with suppressed activities of both enzymes.…”
Section: H354supporting
confidence: 81%
See 2 more Smart Citations
“…Based on the unaltered expression of SIRT3 but increased expression of GCN5L1, we propose that GCN5L1 may be a key modulator of protein acetylation in the heart during maturation. This notion is supported by our recent studies in which increased GCN5L1 contributes to an increase in acetylation of LCAD in obese mice with heart failure, which, in turn, enhances fatty acid oxidation rates (52). As a proof of the concept, we further demonstrated that the inhibition of GCN5L1 in H9c2 cells via siRNA attenuated the levels of acetylated LCAD and ␤-HAD, as well as total protein acetylation, in parallel with suppressed activities of both enzymes.…”
Section: H354supporting
confidence: 81%
“…For instance, hyperacetylated LCAD has been suggested to reduce enzymatic activity in the liver and the heart from SIRT3-deficient mice (9,19), and LCAD Lys 42 , Lys 318 , and Lys 322 were detected as a critical active site for the regulation of LCAD enzymatic activity by SIRT3 (2, 4). However, we have demonstrated that increased acetylation of LCAD and ␤-HAD is associated with an increase in fatty acid ␤-oxidation rates in hearts from mice with SIRT3 deficiency, as well as in mice with a high-fat diet-induced obesity, and in mice with heart failure (1,52). Because previous studies were carried out in males and similarly aged animals, gender or age effects are unlikely to occur in those experimental settings (1,10,52).…”
Section: H354mentioning
confidence: 91%
See 1 more Smart Citation
“…At 6 wk of age, mice were placed on pellets of either a normal chow diet (NCD) consisting of 24.7% energy from protein, 63.4% carbohydrate, and 4.6% fat (PicoLab rodent diet 5053, 339.5 kcal/100 g, TestDiet, Richmond, IN) or a HFD consisting of 14.9% energy from protein, 26.0% carbohydrate, and 59.0% fat (S3282, 549.0 kcal/100 g, Bio-Serv, Frenchtown, NJ) for 12 wk. Previous studies have demonstrated that a 60% fat diet induces insulin resistance as well as obesity and creates a reasonable model for studying pathophysiological features of the cardiovascular system in diet-induced obesity (8,25,41). To evaluate HFD-induced glucose intolerance and insulin resistance, we performed glucose tolerance tests (GTTs) and insulin tolerance tests (ITTs) after 12 wk of NCD or HFD feeding as previously demonstrated (4,36).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, caloric restriction‐induced cardioprotection has been suggested to be mediated through an age‐independent manner . In a model of high fat (HF) diet‐induced obesity and diastolic dysfunction, we recently reported that lowering body weight by switching mice to a low fat (LF) diet improves cardiac insulin sensitivity and function . However, the impact of weight loss by CR on cardiac hypertrophy, energy metabolism and function in heart failure associated with obesity is not known.…”
Section: Introductionmentioning
confidence: 99%